The Effect of Leadership Style on Turnover Intention and Job Satisfaction - Setyo Widodo, Djoko (Greenation Publisher & Yayasan Global Research National, 2023)
The Literature Review article on the Influence of Leadership Style on Turnover Intention and Job Satisfaction is a scientific article that aims to build a research hypothesis on the influence of variables to be used in further research, within the scope of Human Resource Management. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this study are: 1) Leadership Style influences Turnover Intention; 2) Leadership Style influences Job Satisfaction; and 3) Turnover Intention affects Job Satisfaction. Apart from the exogenous variables above that affect turnover intention and job satisfaction, there are other factors including salary, workload, work environment, colleagues and career development.